Coronavirus - current medical and social problem - Anna Welz; Anna Breś-Targowska (Polish Pharmaceutical Society, 2020)
Coronaviruses can be divided into two groups due to pathogenicity. The first group causes mild upper respiratory tract infections. The second group includes highly pathogenic coronaviruses, which are the cause of severe pneumonia. In December 2019, the emergence of a new 2019-nCoV coronavirus was reported in the human population, which caused a pandemic. Cases of pneumonia have been reported in patients. Complications included: acute respiratory distress syndrome, anaemia, acute myocardial injury, secondary infections and in severe cases - death of patients. Viral factors and host immune responses were important in the development of infection. The course of the disease also depended on: initial viral load in the respiratory tract, comorbidities and the age of patients. Younger people experienced milder symptoms, and older people had more severe disease. Diabetes, hypertension, cardiovascular disease and renal failure were the most frequently mentioned comorbidities. The therapeutic problems concerned the need to develop effective CoV treatment regimens. Late diagnosis is often the cause of a complex situation that requires intervention in intensive care units. There are still no approved antiviral drugs and vaccines to prevent SARS-CoV infection. One of the therapeutic solutions is to change the purpose of various approved medicines used in other diseases. Another problem is the transmission of infection, which occurs between people as a result in close and direct contact. Rules for protection against infection have been introduced. Personal protective equipment has been used: gloves, aprons, protective masks and glasses. In addition, the transmission of the infection in indirect contact with contaminated objects is of great importance. Monitoring the epidemiological situation and providing timely information is very important to ensure the safety of the public during and after the pandemic. The purpose of this article is to present the characteristics of the new 2019-nCoV coronavirus and its ability to multiply in the human body. Pathogenic types of coronaviruses, current infection, symptoms, diagnostic methods, treatment and infection transmission, and psychological effects of quarantine are discussed.